Pengembangan Media Pembelajaran Kalkulator Fisika-Induksi Elektromagnetik Berbasis Adobe Flash Pro CS6 - Siwi Puji Astuti; Alhidayatuddiniyah T.W. (SAP (Susunan Artikel Pendidikan), 2018)
The purpose of this research are to: (1) produce a  Physics Calculator application for Junior High School (SMP) based on Adobe Flash with study of material of Electromagnetic Induction and (2) to know the feasibility of the Physics Calculator application. This application has a model of physics formula based on basic competence, with animation on each material and exerciseand the model referring to the UN CBT standard. Besides, the completion output on this application provides the solution. The research and development method used refers to the concept of ADDIE. Menus and features of the application have been adjusted to the design, so it can work well on Windows Operating System. The feasibility test of Physics Calculator application is carried out by distributing the assessment sheets to the media experts and to 9th grade students at SMPN 251 Jakarta and SMPN 203 Jakarta, with the result of 88.63%, 93.83%, and 93.38% respectively. The average validation percentage is 91.94%.So, it can be concluded that this physics calculator app is categorized valid. This application is expected to optimize the 9th grade students’ understanding of subject materials through animated media based on Adobe Flash Pro CS6.